On the exclusion of the evidence of accused persons - O'Hagan, John (Statistical and Social Inquiry Society of Ireland, 1875)
Some apology is, I feel, due to the Society for the selection of a subject so often discussed here and elsewhere; yet when the topic is a proposed reform, it can hardly be said to be exhausted until either it has been carried, or else plainly rejected by public opinion. So far has the latter been from the truth as regards the measure here dealt with, that for many sessions past its proposal and adoption would have seemed no more than the natural completion of the progress already made in the amendment of the ]aw of evidence.
Read before the Society, 18 May 1875
Keywords: Law of evidence; Evidence of accused person; 314.15